Targeted therapies in non-small cell lung carcinoma: what have we achieved so far?. (July 2013) - Farhat, Fadi S.; Houhou, Wissam
The search for innovative therapeutic agents in non-small cell lung cancer (NSCLC) has witnessed a swift evolution. The number of targeted drugs that can improve patient outcomes with an acceptable safety profile is steadily increasing. In this review, we highlight current drugs that have already been approved or are under evaluation for the treatment of patients with NSCLC, either in monotherapy or combined therapy for both the first- and second-line settings. Experience with drugs targeting the vascular endothelial growth factor and its receptor, as well as the epidermal growth factor receptor is summarized. Moreover, we provide an overview of more novel targets in NSCLC and initial experience with the respective therapeutic agents.